(untitled) (Journal of Material Science and Technology Research, 2023)
Abstract: In this study, we explored the development of epoxy resin nanocomposites with 0.1, 0.3%, and 1.0% by weight of aluminum nanoparticles. These nanocomposites were evaluated for mechanical properties (tensile test and Izod strength test) and thermal properties (differential scanning calorimetry and thermogravimetric analyses), and their morphology was assessed using field emission gun scanning electron microscopy. Adding even small amounts of aluminum nanoparticles led to notable improvements in the mechanical and thermal resistance. Remarkably, composites with 1.0 wt% of aluminum nanoparticles presented a 25% increase in the elastic modulus, a 20 °C increase in the glass transition temperature, and a 30 °C increase in the degradation temperature. These findings hold significant promise for advancing the field of polymer-metal nanocomposites.